NILAI MORAL BAHASA JAWA dalam FILM PENDEK “PITUTUR 2” - Iin Nur Zulaili (Qurthuba: The Journal of History and Islamic Civilization, 2023)
Abstract: This article identifies and analyzes the forms of moral values ​​found in the short Javanese film “Pitutur 2” produced by Paniradya Kaistimewaan using James Rachels' theory. This research was studied using a literary psychology approach. The method used is descriptive qualitative by interpreting the analysis of the data contained in the film. Data collection techniques use content analysis techniques to explain the data that has been found. The data found in this study are in the form of data excerpts from the dialogue between characters, the behavior of the characters, and the speech obtained by the characters. The results of this study are the relevance between educational values ​​in film and Javanese pitch, there are; 1) Tresnane wong tuwo nang anak.e tan kena kapitung mawa amba; 2) Gusti peparing akal lan pikiran supoyo ngerti endi tumindak ala utawa becik; 3) Pangibadah ing lelaku supoyo urip urup, migunani lan tansah mertobat. Keywords: Javanese Pitutur, Moral Values, and Javanese Language